2016
DOI: 10.17508/cjfst.2016.8.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic and total flavonoid content variability of soybean genotypes in eastern Croatia

Abstract: Indexing p. 1  Editorial Bord p. 1  Guide for Authors p. 3  Manuscript preparation p. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 0 publications
3
22
0
3
Order By: Relevance
“…Kurva standar kuersetin disiapkan dengan konsentrasi 0, 25, 50, 75, 100, 125 mg/l, persamaan kurva standarnya y=0,0027x+0,0524 dengan R 2 = 0,9984). Konsentrasi flavonoid dalam sampel uji dihitung dari standar kalibrasi dan dinyatakan sebagai ekuivalen kuersetin dalam mg/g sampel (Josipovic et al, 2016).…”
Section: Prosedur Penentuan Total Fenolikunclassified
“…Kurva standar kuersetin disiapkan dengan konsentrasi 0, 25, 50, 75, 100, 125 mg/l, persamaan kurva standarnya y=0,0027x+0,0524 dengan R 2 = 0,9984). Konsentrasi flavonoid dalam sampel uji dihitung dari standar kalibrasi dan dinyatakan sebagai ekuivalen kuersetin dalam mg/g sampel (Josipovic et al, 2016).…”
Section: Prosedur Penentuan Total Fenolikunclassified
“…Adetutu et al (2015) reported 0.05 mg/g of flavonoids in watermelon seeds. In contrast, henna, pomegranate and soybean seeds reportedly contain 1.10, 6.79 and 0.580 mg/g, respectively (Cherbi et al, 2016;Elfalleh et al, 2012;Josipovic et al, 2016). However, phenolics quantified were found to be significantly lower than previously reported by other researchers.…”
Section: Total Phenolics Flavonoids and Antioxidant Activitymentioning
confidence: 81%
“…TFC was determined spectrophotometrically using a colorimetric method based on aluminum chloride (AlCl3) with minor modifications [29][30][31]. A sample (2 mL) was mixed with NaNO2 solution (0.6 mL, 5%, w/v), followed by the addition of AlCl3 (1 mL, 2%, w/v) after 5 min.…”
Section: Determination Of Total Flavonoids Content (Tfc) Of the Highementioning
confidence: 99%